Addressing Vandalism Behavior through the Management of Guidance and Counseling Services in Periphery Schools of Indonesia and Malaysia - Ifadatut Thausiyah; Hidayat, Rofiq (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to explore how the handling of vandalism behavior can be done through the management of guidance and counseling services at SMAN 1 Yosowilangun Lumajang and some Malaysian schools. The research method used is qualitative with a case study approach. Data collection was carried out through semi-structured interviews, passive observation and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. Data validity was tested using source and method triangulation. The results of the study indicate that preventive actions carried out by means of socialization and punishment in the form of replacing and repairing damaged facilities which are then recidivists, namely by conducting coaching with member of the Indonesian National Army in collaboration with Yonif 527 Lumajang. And also the results of research in Malaysian schools that the main factors that cause students to behave vandalism are the attitudes of the students themselves, as well as family background factors and peer influence. The role of parents, the role of schools, and the role of social media are steps that can be taken to overcome the problem of vandalism behavior.